HUBUNGAN PENYESUAIAN DIRI REMAJA TERHADAP MOTIVASI BELAJAR SISWA XI SMK PANCA ABDI BABGSAKU STABAT-LANGKAT SUMATERA UTARA - Sri Ramadhani; Dwi Nursiti; Siska Dwi Ningsih; April Yanus Dachi (Psikologi Universitas Sari Mutiara Indonesia, 2019)
The purpose of this study is to know the relationship adolescent adjustment self to the motivation to learn grade students XI. Background research this is done because it is based observation which researchers do, found that the motivation to learn students SMK Panca Abdi Bangsaku still lacking in ability adjust oneself the less good inside interacting with teachers and fellow students This researcher is research quantitative with a study approach product moment correlation. Population research This is students of SMK Panca Abdi Bangsaku. Amount sample as many as 76 students class XI SMK Panca Abdi Bangsaku. Technique sampling used that is cluster random sampling. Data Research taken by using communication techniques indirectly that is distributed questionnaires using the likert scale of both adolescent adjustment self variables and learning motivation variables The frequency distribution results show that the ability alienation self-students SMK Panca Abdi Bangsaku still in the moderate category, while the level of motivation to learn students SMK Panca Abdi Bangsaku still at a moderate level. The results show the relationship between variable adolescent adjustment self and variable learning motivation amount rxy = 0.332. Results testing hypothesis shows that value correlation rxy = 0.332 > value r tabel = 0.224, then Ha is accepted meaning there is a relationship between adolescent self- adaptation to the motivation of learning students SMK Panca Abdi Bangsaku North Sumatra.